Il ruolo di Posidonio e della dossograﬁa per la datazione del Περὶ κόσμου e i rapporti con l’Elogium geographiae. II - Lucarini, Carlo M.; Scermino, Maria (Hyperboreus, 2019)
The paper deals with the problem of the inﬂuence of Posidonius’ teaching on Περὶ κόσμου and puts forward arguments against attempts, some of them quite recent, to attribute this treatise to Aristotle. § 1 oﬀers a short history of how Περὶ κόσμου has been interpreted, while § 2 outlines the current status quaestionis. § 3 demonstrates that Theophrastus’ doctrines on the origin of earthquakes and of high tides do not correspond to those of Περὶ κόσμου. § 4 and 5 adduce evidence that the scientiﬁc views of Περὶ κόσμου derive from the doxographic tradition and not directly from Aristotle’s Meteorology. In § 6, the deﬁnition of the rainbow given in Περὶ κόσμου is analyzed: the presence of keywords such as κοῖλος and τμῆμα proves inter alia that it comes from Posidonius’ theory on the origin of rainbows. Περὶ κόσμου is thus deﬁnitely post-Posidonian. The aim of the ﬁnal paragraph is to demonstrate that the anonymous Elogium geographiae (a part of the famous P. Artemid.) has been inﬂuenced by the proem of Περὶ κόσμου. This allows us to date the Elogium very closely to the turn of the Christian era.